The teacher's attention : why our kids must and can get smaller schools and classes - Delavan, Garrett, 1973- (Temple University Press, 2009)
The Teacher & rsquo;s Attention is a fresh take on relationships in schools. Looking beyond our obsession with raising test scores, this book recognizes that education is a key partner in raising children. Garrett Delavan contends that allowing students, educators and parents to navigate a smaller number of relationships & mdash;a concept he calls "relationship load" & mdash;provides many benefits, including a better chance at achieving equal access to a good education for all children. Delavan shows how class size, school size, and longer-term student-teacher relationships are all equally